MENTAL TRANSLATION IN THE WRITING PROCESS: A CASE STUDY OF INDONESIAN EFL UNIVERSITY STUDENTS - Maharani, Ida Ayu; Dewi, Ni Putu Dilia (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2025)
Mental translation, the internal process of formulating ideas in a first language (L1) before expressing them in a second language (L2), remains a common yet underexplored strategy among English as a Foreign Language (EFL) learners. In Indonesia, where academic writing in English is a key component of university education, students frequently rely on this process, particularly during complex writing tasks. This study investigates how Indonesian EFL students experience and perceive mental translation during English writing. Using a qualitative case study approach, data were collected from 60 students at ITB STIKOM Bali through open-ended questionnaires and follow-up interviews. Thematic analysis revealed that students often begin the writing process by thinking in Indonesian, especially when working on formal or cognitively demanding texts. While many find mental translation helpful for organizing thoughts and reducing anxiety, it also contributes to slower writing speed, overthinking, and a reliance on digital translation tools. The study draws on Flower and Hayes’s (1981) Cognitive Process Theory of Writing, Kroll and Stewart’s (1994) Revised Hierarchical Model, and Vygotsky’s (1978) Sociocultural Theory to interpret mental translation not as a sign of linguistic deficiency, but as a mediational strategy that supports meaning-making. The findings highlight the need for more inclusive EFL writing instruction that acknowledges mental translation as a valid part of students’ cognitive process, while also encouraging gradual development of direct composition in English.